Mediação de conflitos na escola pública à luz da educação em direitos humanos: empoderando-(se) pelo diálogo - Leite, Djamere de Sousa Braga (2019)
The objective of this work is to analyze, in the light of Human Rights Education, the transformative mediation of conflicts by social mediators of a public school in Fortaleza, CE, regarding the empowerment of the subjects through dialogue, to answer two central questions: conflicts in school, what are the effects of Transformative School Mediation? Has mediation fostered a culture of dialogue and fostered the empowerment of the school community? The methodological approach adopted was qualitative and the case study was adopted as a research strategy. For the data collection, interviews, focus group, documentary research and field diary were used. Regarding the treatment, the interviews and the focus group had their audio records transcribed literally and the school documents were completely read and photocopied. The field diary notes were handwritten and used as the research memory. In order to answer the research questions, we analyzed experiences in a public school in Ceará that, at the time of data collection, dealt with the mediation of conflicts, in order to establish, through this intervention, according to the interpretation developed here, a education in and for Human Rights. It was analyzed how, through mediation, conflict resolution processes led to dialogue and the empowerment of its participants, as provided by the political and educational guidelines of an education focused on Human Rights. Assuming that a dissertation in the field of Human Rights should collaborate with processes that contribute to the dignity of the human person, it was observed that this peaceful method of conflict resolution became public policy in the school when it was found that the security strategies the violence, did not have the desired effects. Thus, despite all efforts to establish a culture of peace in the state of Ceará, conflicts that converge to violent acts still reach school, which, bombed intra and extramuros, need to develop strategies for local survival. In this context, the history of public policies to prevent / manage conflicts in the Brazilian cultural context has evidenced that mediation is a more effective and educational way. In the researched school, the perception of conflicts persisted, but how to overcome them became more educational: peer mediation, which, as the interview data, focus group and observations show, improved the means for solving conflicts. Therefore, student empowerment and protagonism were perceived in the findings of this research, since the adolescents participating in the school mediation case demonstrated internal and external changes. In the analysis of a case of horizontal mediation, it was recognized the empowerment through dialogue, since the mediators provide the voice parts in the resolution process, encouraging them to reach an agreement, bringing, therefore, an improvement in the school climate and coexistence. It is also perceived that in the activity of mediators, students play their roles as active citizens, aware that they are subjects of law, from the moment they are known and recognize in the other the extent of the damage caused, the focus is not on conflict. Thereby, the transformative mediation of school conflicts, whose focus rests on the recomposition of human relations, is linked to human rights education, since it provides dialogic processes, diminishes the authoritarianism of power existent and generates the empowerment of the subjects as active citizens.